Examining a "Household" Model of Residential Long-term Care in Nova Scotia - Janice Keefe; Donna Dill; Rachel Ogilvie; Pamela Fancey (McMaster University Library Press, 2017)
In 2006, Nova Scotia began to implement its Continuing Care Strategy which was grounded in a vision of providing client-centered care for continuing care clients, including residents of nursing homes. Considerable evidence pointed to the benefits of the "household" model of care-which led the province to adopt the smaller self-contained household model as a requirement for owners/operators seeking to build government-funded new and replacement nursing homes. The specific goals of the reform (the adoption of the household model) included increasing the proportion of single rooms, improving the home-likeness of the facility, and more generally, providing high-quality care services. The reform was influenced by recognition of the need for change, rapid population aging in the province, and strong political will at a time when fiscal resources were available. To achieve the reform, Nova Scotia Department of Health released two key documents (2007) to guide the design and operation of all new and replacement facilities procured using a request for proposal process: The Long Term Care Program Requirements and the Space and Design Requirements. Results from a research study examining resident quality of life suggest regardless of physical design or staffing approach high resident quality of life can be experienced, while at the same time recognizing that the facilities with "self-contained household" design and expanded care staff roles were uniquely supporting relationships and home-likeness and positively impacting resident quality of life. La Nouvelle-Écosse a lancé en 2006 la mise en oeuvre de la Stratégie pour les Soins de Longue Durée, bâtie sur l'idée de procurer des soins centrés sur le client pour ceux ayant besoin de soins de longue durée, y compris les résidents des institutions. Les avantages du modèle de soins dit de "domicile" étaient amplement démontrés empiriquement, ce qui a conduit la province à imposer aux propriétaires ou opérateurs cherchant à construire ou rénover des institutions de long-terme financées par le gouvernement un modèle de logement autonome de petite taille. La réforme (adoption du modèle de domicile) avait pour objectifs spécifiques d'accroître la proportion de chambres simples, de rendre l'institution plus proche d'un domicile privatif, et, plus généralement, de procurer des services de très bonne qualité. La réforme a été motivée par la reconnaissance d'un besoin de changement, le vieillissement rapide de la population de la province, et une forte volonté politique à une époque où les ressources fiscales étaient encore abondantes.  Pour réussir la réforme, le Ministère de la Santé de Nouvelle-Écosse a publié deux documents clé (2007) détaillant la conception et le fonctionnement de toutes les institutions créées ou rénovées à travers un appel d'offres: les normes du programme de soins de longue durée, et les normes d'espace et d'agencement. Une étude mesurant la qualité de vie des résidents a montré que, si une qualité de vie élevée pouvait être atteinte quels que soient l'agencement physique et la dotation en personnel, les institutions organisées en domiciles autonomes et confiant plus de responsabilités aux soignants étaient idéalement placées pour encourager la socialisation et le sentiment d'être chez soi, et influencent donc positivement la qualité de vie.